An Interview Regarding Enactivism - Ellis, Ralph D. (Eidos. A Journal for Philosophy of Culture, 2024)
Preview: / Ralph D. Ellis interviewed by Samuel Maruszewski / Ralph D. Ellis, one of the strongest advocates of the enactivist approach to consciousness and cognitive theory, began his academic career as a phenomenologist, earning the Ph.D. at Duquesne University under Andre Schuwer, John Sallis and Amedeo Giorgi, and has taught at Clark Atlanta University since 1985. He subsequently received a post-doctoral M.S. in Public Affairs at Georgia State University, and worked also as a social worker in both Pittsburgh and Atlanta. Partly as a result of those experiences, as well as being a life-long practitioner of Gene Gendlin’s focusing method, he gravitated toward emotion research and the intersection of philosophy, psychology and the brain sciences from the enactivist perspective, arguing that action, as opposed to mere reaction, has to be emotionally motivated, and that the understanding of all modalities of consciousness should include that perspective. The author of many books and articles on these topics, he is interested in integrating the social sciences with phenomenology, ethics, and philosophy of mind. He is now trying to integrate enactive consciousness theory with moral and social philosophy, with relevance to our current world-wide crisis of internet disinformation. The Moral Psychology of Internal Conflict (Cambridge University Press 2018) is an attempted beginning in that direction. His latest book, Action, Embodied Mind, and Life-World (SUNY Press 2022) is a continuation of that project. His various books in these areas are listed at the Ralph D. Ellis page of Amazon.com.